Spatial differential analysis of the intensity distribution for a collimated wave beam - Blank, A.V.; Suhareva, N.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2020)
A method for the comparative analysis of intensity distribution profiles is proposed on the basis of the image structure tensor. The parameter set of the local tensor array introduced for each pixel of the recorded image is used to determine the spectrum of local orientations, the energy intensity profile of the image, and the coherency of its structure. The proposed method is important for the discrete analysis of space-time structures of wave beams transmitted through the regions of localized or distributed refractive noises.